(untitled) (Research, Society and Development, 2021)
The evaluation and intervention on pain should be priority activities in the professional performance in the hospital context since it impacts the quality of life. Therefore, this integrative literature review aimed to identify, in the Brazilian and international literature, strategies for the development of health education on pain in the hospital. The selection of the studies took place, between February and March 2020, in the databases Scientific Electronic Library Online (SCIELO), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Scopus, Pubmed, and Web of Science. We identified 449 articles and, among them, after applying the inclusion and exclusion criteria, 17 composed the empirical material of analysis. We organized the information extracted from the studies in a spreadsheet of the Microsoft Excel program, the level of evidence of the publications was evaluated, and the analysis was based on the synthesis and proximity of the types of health education strategies. The results addressed three groups of strategies recommended for use with health professionals, patients, and caregivers, including digital technologies, group and psycho-educational strategies, and booklets and printed materials. We found that most of the studies presented a strong recommendation based on the level of evidence. Videos, games, booklets, psychodrama, and online platforms are more attractive, interactive, and accessible strategies. These strategies can be incorporated during hospitalization, in order to favor the understanding and protagonism of patients and their caregivers in pain control, as well as can be used with students and health professionals.